ANALISIS PENGARUH PRODUK DOSMESTIK BRUTO (PDB), INFLASI, DAN KURS TERHADAP IMPOR DI INDONESIA TAHUN 1991 - 2020 - Oktavia, Shindy (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study was to find out the relationship between GDP, inflation and exchange rates on imports in Indonesia in 1991 – 2020. Import is the process of legally transporting goods or commodities from one country to another, generally in the process of trade. If in a country imports increase then the country's national income will decrease. Countries that often import are developing countries, for example Indonesia. Therefore, the method that can be used is the VAR method. and the data used is quantitative data, because the data used to calculate the effect on import variables. The source of financial data is used as secondary data, which is data obtained from official sites or websites. The results of this study are that the inflation variable has a greater relationship than GDP and exchange rates.